Infringement of European Union trade marks on the Internet and Private International Law - Lorente Martínez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
With the attention given to the recent judgment of the CJEU of 5 September 2019 this work makes an analysis of the issues of private international law relevant with regard to the infringement of the European trade mark in an international context. The Court of Justice has issued a judgement on international jurisdiction in connection with the special ground on the subject as declared in Art. 7.2 of the Brussels I bis Regulation.